THE USE OF THE TERMS «MINIMUM WAGE» AND «LIVING WAGE FOR ABLE-BODIED PERSONS» IN ORDER TO IDENTIFY THE SIGNS OF OFFENSES IN THE FIELD OF ANTI-CORRUPTION FINANCIAL CONTROL - Михайленко, Дмитро Григорович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the doctrinal interpretation of Art. 172-6 the code of Ukraine about administrative violations and Art. 366-1 of the Criminal Code of Ukraine, in part of the calculation in monetary terms, of the magnitude of the discrepancy between deliberately false information in an anti-corruption declaration in relation to property or other object of declaration, which has value, and reliable information regarding such objects. Results: it was concluded that the retroactive effect of the law in time (the norms provided for in Part 4 of Article 172-6 of the Code of Administrative Offenses and Part 1 of Article 366-1 of the Criminal Code of Ukraine) in connection with the adoption of the Law of Ukraine «On Amendments to Some Legislative Acts of Ukraine» of 06.12.2016 and in connection with the increase of the subsistence minimum for able-bodied persons in accordance with Art. 7 of the Law of Ukraine «On the State Budget of Ukraine for 2017» does not arise. Discussion: the necessity in the development of the doctrinal basis of criminal lеgislation is grounded in order to prevent changes in the criminal law influence on legal relationships not planned by the legislator.